The Analysis Of Peat Soil Biological Characteristics After Being Incubated Using Vermicompost From A Mixture Of Chicken Dung, Banana Hump, And Tofu Waste - Ade Tri Darma; Hilwa Walida; Siti Hartati Yusida Saragih; Khairul Rizal (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Peatlands are formed from piles of trapped plant residues, obstructing their decomposition process. The organic matter decomposition process certainly involves soil microbes. This study aims to determine the biological characteristics of peat soil after incubation with vermicompost. This research was conducted at Kampung Perlabian Village, Kampung Rakyat Sub-district, South Labuhanbatu Regency, North Sumatra. Soil biological analysis was conducted in the soil biology laboratory, Faculty of Agriculture, University of North Sumatra. This study used a non-factorial Randomized Block Design (RAK) with three treatments: P0 (control), P1 (1 kg peat soil + 500-gram vermicompost), and P2 (1 kg peat soil + 1 kg vermicompost). The results showed that adding vermicompost fertilizer to peat soil with treatment two could increase the total bacteria by 6.17 x 106 cfu/ml and the total fungus by 8.8 x 105cfu/ml, and CO2 respiration by 4.125 (mg CO/day). As a result, the soil's microorganism's activity is a process in which microorganisms live and do activities in a soil mass.